Accurate calibration of mutual coupling for conformal antenna arrays. Issue 23 (1st November 2013) - Huang, Qiulin; Zhou, Hongxing; Bao, Jian; Shi, Xiaowei
Abstract : The element pattern reconstruction method is proposed to calibrate the mutual coupling effect of conformal antenna arrays. The calibration matrix due to the proposed calibration method is obtained through the transformation of element patterns rather than the analysis of currents or voltages on the antenna array, which is different from previous calibration methods. The new method can provide effective mutual coupling calibrations for conformal antenna arrays. A conformal microstrip array is designed to verify the effectiveness of the new calibration method.